Evaluation of Heavy Metals Contamination of Soil and Vegetation in the Vicinity of a Cement Factory in the Volta Region, Ghana - Addo, M.A.; Darko, E.O.; Gordon, C.; Nyarko, B.J.B.; Gbadago, J.K.; Nyarko, E.; Affum, H.A.; Botwe, B.O. (International Journal of Science and Technology, 2012)
Heavy metal mobilization in the biosphere by human activities has become an important process in the geochemical recycling of these metals. In this work, 34 soil samples and 29 Tephrosia elegans plants collected in the vicinity of the Diamond Cement Factory, Aflao, Ghana were analyzed for As, Co, Cr, Cu, Mn, Ni, Pb and Zn using energy dispersive XRF. The results of the metal analysis indicated that some metallic levels were in excess of natural background and critical limits for the soil and plants respectively. The results further revealed that the metal distribution were in a fluctuating manner considering various distances and directions from the cement facility. However, it was observed that the mean metal concentrations of the soil and plants decrease as distance from the cement facility increased for most metals. This indicated that the facility which is the only industrial source in the area is the major cause of the pollutants contamination in its vicinity. In an attempt to understand the pattern of metal contamination in the area, useful tools including enrichment factor, geoaccumulation index and pollution load index were employed to indicate the sources of soil contamination were anthropogenic in character. Recommendations for the need for other studies on environmental and human health around the cement and similar facilities to protect human life and the environment are suggested.
Keywords: Heavy metal; Contamination; Geoaccumulation index; Vegetation; Cement facility; Toxicity